Self-Help Groups and Women Entrepreneurship in India : Opportunities and Challenges - Yadav, Jyoti (AMC Indian Journal of Entrepreneurship, 2021)
The number of women entrepreneurs is increasing all over the world but the condition of women in developing nations is different from that of women in developed countries. In India, the empowerment of women is an important issue as the condition of rural women is still very pathetic. Government of India is taking various initiatives for the development of women and for improving their economic condition. Self-help group (SHG) programme has proved to be an effective programme for empowerment of women. SHGs provide financial facilities to rural women which helps in starting entrepreneurial activities and motivating women for establishing new small businesses. Women are participating in training and capacity building programmes and are utilizing the loan amount for income-generating activities. SHG members take mutual decisions related to production and marketing. Secondary sources of data were used for fulfilling the purpose of the paper. This paper attempted to explain the role of SHGs in women entrepreneurship development. It highlighted the opportunities provided through SHGs as well as through different schemes of government for entrepreneurship development. The challenges in the way of women entrepreneurs are also discussed. The result of the study will help policymakers in framing policies for the development of women entrepreneurs and provide future direction to researchers.